Impact of perceived auditor independence on going concern audit opinions for financially distressed companies in Malaysia - Dharmaraj, D. Joyce Christina (2016)
With the public outcry over the corporate scandals across the world, such as Enron and WorldCom in the U.S., as well as Transmile and Silverbird in Malaysia, the notion of auditor independence has received substantial attention from the profession and regulatory bodies worldwide. These scandals involving listed companies have highlighted concerns of regulators and other interested parties relating to threats towards auditor independence. In Malaysia, the Malaysian Code on Corporate Governance (MCCG) was introduced in March 2000 (revised in 2017) as a result of recommendations made by the Finance Committee on Corporate Governance (FCCG). MCCG highlights the need to reinforce the independence of the external auditor. However, it is noted that when organisations are in financial distress, auditors do not provide signals of potential distress, i.e. Type II Misclassification, which triggers independence of the auditors. Hence, there is a need for identification of determinants of auditor independence that leads to impairment and compromisation of perceived auditor independence to maintain the credibility of the auditing profession. It is necessary to develop a tool to assess auditor independence based on observable data from published reports. It is also critical to investigate the relationship between auditor independence and the going concern audit opinions for financially distressed companies in Malaysia to understand how to increase confidence and rebuild trust in audit opinions of financial statements, which are important to ensure capital market growth. In this study, twenty four publicly available variables were used to examine the determinants of auditor independence in financially distressed companies. A total of 750 questionnaires were distributed among accountants (MIA-registered practitioners) to capture auditors’ perception on auditor independence since actual independence cannot easily be observed or assessed. The study found that the determinants of auditor independence for financially distressed Malaysian companies are namely, (1) Disclosure and Financial Performance, (2) Relationship-centric, (3) Ethnicity, (4) Assurance Focus, and (5) Transparency Focus. Based on the findings of this study, Auditor Independence (PAI) Index was developed and validated using Altman’s Score. Archival data of 78 financially distressed Malaysian companies (i.e. PN17 companies) in the period between 2007 and 2012 were utilised to compute the respective PAI value. This period was chosen to assess the perception of auditor independence before the release of the revised MCCG 2012 which explicitly addresses the importance of auditor independence. It was found that relationship-centric and ethnicity determinants are statistically significant to predict PAI value using published data. Higher PAI value reflects impaired auditor independence. In addition, the study also revealed that auditor independence has a negative impact on issuance of going concern opinions. Besides contributing to the literature, this research is useful for policymakers, financial statement users, and audit professionals to understand factors that can impair or compromise auditor independence.